I Only Cry with Emoticons - Zalkow, Yuvi (Book collections on Project MUSE., 2022)
"Saul doesn't get why he's misunderstood. At his high-tech day job, he hides in the bathroom writing a novel about his dead grandfather and wonders why his boss wants to fire him. He tells his almost ex-wife about a blind date and wonders why she slams the door in his face. He aches with worry for his seven-year-old son, who seems happier living with his mom and her new man. When the blind date becomes a complicated relationship, and Saul's blunders at work threaten the survival of the company, Saul has to wake up and confront his fears. I Only Cry with Emoticons is a quirky comedy that reveals the cost of being disconnected--even when we're using a dozen apps on our devices to communicate--and an awkward man's search for real connections, on and offline"--